Formulated citrus peel extract gold lotion improves cognitive and functional recovery from traumatic brain injury (TBI) in rats - Cheng Guang; Yue Zhiwei; Wang Liwen; Miyauchi Yutaka; Suzawa Michiko; Li Shiming; Ho Chi‐Tang; Zhao Hui; Chen Naiyao (Food Science and Human Wellness)
Traumatic brain injury (TBI) is closely related to neuro-inflammatory response and causes a complex pathological process and serious consequence. In this study, we explored whether the formatted citrus peel extract gold lotion (GL) could have a therapeutic effect on rats suffered TBI. TBI rat model was prepared by the electric Cortical Contusion Impactor (eCCI) device. Prevention against TBI by GL was assessed by the behavioral, organizational of rats and the molecular markers in the brain injury area. The results showed that GL could reduce nerve damage and neurological dysfunction. The mechanisms probably due to that GL could not only reduce the associated damage markers including GFAP, OX-42, TNF-α, COX-2, NF-κB and TLR4 but also promote the expression of VEGF which is responsible for protecting neuronal cells in the injury area. These findings revealed that GL could be a promising preparation for TBI prevention.